Analisis perbandingan fokus layanan keuangan Baitul Maal wat Tamwil di Indonesia - Aprilian, Rifky Zahrul; Anliwiarta, Zhuvido (Maliki Interdisciplinary Journal, 2024)
This article presents a comparison of the strategic plans of three sharia microfinance institutions, namely BMT Walisongo Papandayan, BMT Umat Mandiri Hidayatullah Balikpapan, and BMT Mirla. These three organizations have different goals and success strategies. BMT Walisongo Papandayan aims to become a trusted sharia financial institution and provide sharia financial services to its members. BMT Umat Mandiri Hidayatullah Balikpapan aims to create visionary organizational managers and increase customer satisfaction. Meanwhile, BMT Mirla consists of two divisions, namely social entrepreneurship and commercial entrepreneurship, with strategic plans that include good financial management and increasing employee productivity.